Estimating inclusion size in WE43-T6 magnesium alloys based on Gumbel extreme values - Ahmad A.; Purbolaksono J.; Yahya Z. (Elsevier BV, 2023)
Estimating the maximum inclusion size in a large volume of clean metal from observations on a small volume is an important problem faced by the metallurgical industries. Static and fatigue behaviors and other mechanical properties of the material are influenced by the maximum inclusion sizes. This paper presents first application of the extreme values method for estimating the largest inclusion in WE43-T6 magnesium alloys. The actual dimensions of the largest pore and oxide in WE43-T6 magnesium alloys are found to be consistent with the dimensions predicted using the Gumbel extreme values (GEV) distribution obtained by both tomography and metallography. In this respect application of the Gumbel extreme values to describe clusters of intermetallic particles and predict the maximum intermetallic size in WE43 magnesium alloys may also be reasonably used. 2009 Elsevier B.V. All rights reserved.